2016
DOI: 10.1039/c6ra04424g
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and magnetism of Co-doped PbPdO2 films with different grain sizes

Abstract: The dependence of the magnetism of the Co-doped PbPdO2 nanograin films with peculiar spin-gapless-related feature on the grain size was studied in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Tang et al . 8 explained the observed coexistence of the ferromagnetism, paramagnetism and antiferromagnetism in Co-doped PbPdO 2 film using a carrier-mediated bound magnetic polaron (BMP) model. Chen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al . 8 explained the observed coexistence of the ferromagnetism, paramagnetism and antiferromagnetism in Co-doped PbPdO 2 film using a carrier-mediated bound magnetic polaron (BMP) model. Chen et al .…”
Section: Introductionmentioning
confidence: 99%
“…From the figures, it is found that the XPS spectra of Pb 4f for three films can be divided into two pairs of characteristic peaks corresponding to Pb 4f 5/2 and Pb 4f 7/2 , which is similarly to previous studied results. 13 From Fig. 4(a) , two pairs of characteristic peaks are described as following: main peaks (136.55 eV, 141.49 eV), and satellite peaks (137.50 eV, 142.20 eV); from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The two peaks stand for Pd 3d 5/2 and Pd 3d 3/2 , which can be attributed to the formation of Pd 2+ . 13,18,19 Fig. 6(a), (b) and (c) shows the XPS spectra of O 1s in PbPdO 2 , PbPd 0.9 V 0.1 O 2 and PbPd 0.9 Gd 0.1 O 2 lms, respectively.…”
Section: Experimental and First-principles Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the distinct different magnetoresistance effects were observed in PbPd 0.9 Cu 0.1 O 2 and PbPd 0.9 Zn 0.1 O 2 , which would be attributed to local structure deformation due to Pd/O deficiencies [ 7 ]. Based on the bound magnetic polaron (BMP) theory, the potential mechanism behind the observed ferromagnetic, paramagnetic, and antiferromagnetic properties coexisting in Co–doped PbPdO 2 film were suggested [ 8 ]. It was suggested that Pd–O hybridization in Co–doped PbPdO 2 thin films were responsible for the transition from weak localization and weak anti-localization [ 9 ].…”
Section: Introductionmentioning
confidence: 99%